Bibliometric Analysis of Decarbonization: Towards Energy Transition and Regional Resilience - Toska, Ermelinda; Chatzitheodoridis , Fotios; Loizou , Efstratios; Kontogeorgos , Achilleas (European Journal of Geography, 2025)
Energy transition through decarbonization has become a cornerstone policy for a sustainable energy future. Enhancing regional resilience is a critical goal for the recovery of local systems from shocks and socio-economic disruptions caused by decarbonization policy. Investigating the consequences of energy transition in regions undergoing decarbonization with emphasis on regional resilience reveals a novel research area. The present study conducts a bibliometric analysis of 535 studies from Scopus published from 2010 to 2024, utilizing VOSviewer and R Studio’s Biblioshiny software for visualization. The data demonstrate publication trends, geographic distribution, collaborations networks, and keyword clusters. A significant geographic inequality emerges. High-income economies dominate the discourse, while low-income countries contribute marginally. Furthermore, the co-occurrence analysis identifies six keyword clusters. Moreover, the thematic evolution depicts the field’s transformation from an embryonic to a mature stage, strengthening core concepts of energy transition, decarbonization, and sustainability, while emerging specialized themes of renewable energy, just transition, and biomass. Finally, the analysis reveals a substantial gap: regional resilience remains underrepresented compared with decarbonization and energy transition, and constitutes a critical challenge for upcoming researchers. Highlights: The transition toward decarbonization generates challenges for coal-reliant regions. Although “regional resilience” was a search criterion, it was absent from the keywords clusters. Regional resilience represents a valuable trajectory for ongoing inquiry.